Transcatheter Treatment of Secondary Tricuspid Regurgitation With Direct Annuloplasty: Results From a Multicenter Real-World Experience. (30th July 2021) - Körber, Maria I.; Landendinger, Melanie; Gerçek, Muhammed; Beuthner, Bo E.; Friedrichs, Kai P.; Puls, Miriam; Baldus, Stephan; Rudolph, Volker; Jacobshagen, Claudius; Arnold, Martin; Pfister, Roman
Abstract : Background: Treatment options for secondary tricuspid regurgitation (TR) remain limited. Early real-world data of a new percutaneous direct annuloplasty system for tricuspid repair were examined. Methods: The first 60 patients treated with the Cardioband tricuspid valve repair system at 4 centers were included in this retrospective study. The primary efficacy end point was technical success with reduction of TR ≥2 grades at discharge. Combined primary safety end point was major adverse events (death, myocardial infarction, cardiothoracic surgery, and stroke) at 30 days. Results: Median patient age was 76 years (73–82), median EuroScore II was 3.9% (2.2–8.1), heart failure with preserved ejection fraction was present in 78%, and 81.7% were in the New York Heart Association class III/IV. Massive or torrential TR was found in 51.7%, and severe TR in 48.3%. The primary efficacy end point was achieved in 45%, while 60.3% of patients had less-than-severe TR at discharge. Vena contracta was reduced by 47% from 12.9±4.8 to 7.0±3.4 mm ( P <0.001). Overall, the majority of patients (81.7%) improved at least by 1 New York Heart Association class. At follow-up 81.3% of patients presented in the New York Heart Association class I or II. The primary safety end point occurred in 4 patients with 2 in-hospital deaths, both not device related. Right coronary artery complications (vessel perforation or stent implantation) occurred in 9 patients (15%). Procedural time decreased from 298 to 185 minutes ( P <0.001) with efficacy remaining stable ( P =0.817) when comparing procedure numbers 11 or more to the earliest 5 procedures per center. Conclusions: This first real-world experience suggests that transcatheter treatment of advanced secondary TR using direct annuloplasty is feasible and reasonably safe early in the learning curve, with significant symptomatic benefit. Further studies are warranted to provide data on long-term outcome and patient prognosis.